1996
DOI: 10.1007/bf00173309
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor-like molecular species in normal bronchoalveolar lavage fluid

Abstract: Normal bronchoalveolar lavage fluid (BALF) contains mitogenic activity for fibroblasts and type 2 pneumocytes. A number of growth factors that might contribute to this activity have been identified in BALF. We found that a molecule or molecules able to bind to epidermal growth factor (EGF) receptors on mouse lung fibroblasts were present in normal mouse BALF and could be blocked by an antiserum to mouse EGF. Receptor binding was partially blocked by preincubation with heparin, indicating a relationship to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…However, we extended these observations by demonstrating glandular expression of TGF-␣, HB-EGF, AR, and BTC in human lung. It is likely that all of these growth factors contribute to the EGF-like growth factor activity that is secreted into the fluid that bathes the apical surface of the bronchial epithelium (53). In our study we also observed immunostaining for EGF, TGF-␣, HB-EGF and AR, but not BTC, between the basal and columnar epithelial cells.…”
Section: Discussionsupporting
confidence: 67%
“…However, we extended these observations by demonstrating glandular expression of TGF-␣, HB-EGF, AR, and BTC in human lung. It is likely that all of these growth factors contribute to the EGF-like growth factor activity that is secreted into the fluid that bathes the apical surface of the bronchial epithelium (53). In our study we also observed immunostaining for EGF, TGF-␣, HB-EGF and AR, but not BTC, between the basal and columnar epithelial cells.…”
Section: Discussionsupporting
confidence: 67%
“…As EGFR levels increase in the skin [22], gastrointestinal tract [23] and lungs [24, 25] in response to tissue injury, the high levels observed throughout the epithelium of severe asthmatic subjects would suggest that there is widespread, ongoing stress and damage in the airways. In normal epithelium, EGFRs are expressed on the basolateral surface [1] and are spatially separate from their activating ligands contained in the apical lining fluid [26]. In contrast, in severe asthma EGFR immunostaining is also evident on the apical surface suggesting the potential for cognate ligand receptor interactions [1].…”
Section: Discussionmentioning
confidence: 99%
“…In these areas of epithelium, membrane staining for the EGFR was particularly intense and was evident on all surfaces including the apical surface (Fig. 1D, F), which is reported to be bathed in secretory fluid containing EGF-like growth factors (37). In contrast, epithelial immunostaining in areas of biopsy-induced damage from normal subjects was not affected (Fig.…”
Section: Analysis Of Egfr Expression In Bronchial Epithelium Of Mild mentioning
confidence: 91%